VALIDITAS MACARTHUR-BATES COMMUNICATIVE DEVELOPMENT INVENTORIES (MB-CDI) DALAM MENGUKUR PERKEMBANGAN BAHASA ANAK USIA DINI SISWA TK DI KABUPATEN BONE - Syam, A. Sri Mardiyanti (Institut Agama Islam Negeri Bone, 2019)
The current era of the fourth industrial revolution places language and technology as a very important skill to be mastered well, this is because all sources of knowledge and information provide language. Therefore, language skills need to be maximized in their early development. In school life, teacher knowledge about children's language is useful for the purposes of planning, implementing, and evaluating learning. Thus the teacher should have extensive knowledge about children's language development and how to develop it, so that one day they have correct and good language skills, both in listening, speaking, reading, and writing.The teacher's demand in knowing and evaluating children's language development from an early age demands the development of a measuring tool that has been spread and used globally by education practitioners in the world, one of which is MacArthur-Bates Communicative Development Inventories (MAB-CDI) Some instruments have long been developed to measure childâ€™s early language development such as Commmunicative Development Inventories (CDI) that developed by MacArthur & Bates. The purpose of this research is to analyze the construct validity of MAB-CDI. Instruments were distributed to 79 students at kindergarden school. Confirmatory Factor Analysis were used to see the good model for dimensions in early communicative development. This validation tried to reveal the suitability of the instruments to measure the kindergarden students' early language development in the Bone context.Â Keywords: Assessment, Early childhood , Language Developmnet, Â